Transcriptomic analyses reveal new genes and networks response to H5N1 influenza viruses in duck (Anas platyrhynchos) - Yin-hua HUANG; Hua-peng FENG; Li-ren HUANG; Kang YI; En-guang RONG; Xiao-yun CHEN; Jian-wen LI; Zeng WANG; Peng-yang ZHU; Xiao-juan LIU; Xiao-xue WANG; Jia-xiang HU; et al. (Journal of Integrative Agriculture, 2019)
H5N1 influenza represents one of the great challenges to public health. Some H5N1 viruses (i.e., A/goose/Hubei/65/05, GS/65) are weakly pathogenic, while the others (i.e., A/duck/Hubei/49/05, DK/49) are highly pathogenic to their natural hosts. Here, we performed brain and spleen transcriptomic analyses of control ducks and ones infected by the DK/49 or the GS/65 H5N1 virus. We demonstrated that, compared to the GS/65 virus, the DK/49 virus infection changed more numerous immune genes’ expression and caused continuous increasing of immune pathways (i.e., RIG-I and MDA5) in ducks. We found that both H5N1 virus strains might escape or subvert host immune response through affecting alternative translation of immune genes, while the DK/49 virus seemed to induce alternative translation of more immune genes than the GS/65 virus. We also identified five co-expressional modules associated with H5N1 virus replication through the weight correlation network analysis (WGCNA). Moreover, we first demonstrated that the duck BCL2L15 and DCSTAMP in one of these five modules inhibited both the highly pathogenic and weakly pathogenic H5N1 virus replication efficiently. These analyses, in combination with our comprehensive transcriptomic data, provided global view of the molecular architecture for the interaction between host and H5N1 viruses.